Characteristics of an outstanding musical talent - a case study - Drovenik Adamec, Tjaša (Revija za elementarno izobraževanje, 2022)
The purpose of this study is to investigate the expression of thirty-two characteristics of a musically talented person in various life periods (from three to thirty-five years of age), in a case study of an internationally renowned musician and organist, Aleksey Vylegzhanin. The results show that the expression of the characteristics of his musical talent increased with age. With enough rehearsal and support from the environmental factor, his characteristics increased to a level above average, compared to his peers. These were also predispositions for the musical development of the organ virtuoso.
Keywords: case study; giftedness; glasbeni talent; izjemen talent; musical talent; nadarjenost; organ virtuoso; orgelski virtuoz; outstanding talent; študija primera